Distribution and Evolution of the Bacteriophage WO and Its Antagonism With Wolbachia - Miao, Yun-heng; Xiao, Jin-hua; Huang, Da-wei (Frontiers in Microbiology, 2020)
The symbiosis system among eukaryotic hosts, intracellular bacteria Wolbachia and temperate bacteriophages WO has a close and intricate relationship among them, which is widely spread through nearly half species of arthropods. Even though bacteriophage WO can have diverse influences on the ecology and evolution of Wolbachia, we still know very little about the distribution and evolution of phages WO. In this study, we discovered for the first time that in an insect group of the fig wasps, the genomes of all the infected Wolbachia strains had only one cryptic prophage WO, which contained defects in the genomic structural modules. This phenomenon was utterly contrary to the widely accepted that Wolbachia with cryptic prophages usually possesses at least one intact WO prophage consisted of gene sequences of the head, baseplate, and tail modules, by which the prophage could form intact virions. In addition to the feature of genetic structure, the phylogenetic relationships of WO and Wolbachia also revealed that bacteriophages WO could horizontally spread among a certain genus or a group of insect hosts, nearly free from the restriction of Wolbachia’s affiliation. Combined with the vertical transmission along with Wolbachia, it could explain the wide spread of WO. Furthermore, the gender preference and functional module preference for transcriptional activity of the genes in cryptic WOs implied the antagonized co-evolutionary pattern between prophages WO and their Wolbachia hosts.